Kinetic Determinants of Reactive Strength in Highly Trained Sprint Athletes. Issue 6 (June 2018) - Douglas, Jamie; Pearson, Simon; Ross, Angus; McGuigan, Mike
Abstract : Abstract: Douglas, J, Pearson, S, Ross, A, and McGuigan, M. Kinetic determinants of reactive strength in highly trained sprint athletes. J Strength Cond Res 32(6): 1562–1570, 2018—The purpose of this study was to determine the braking and propulsive phase kinetic variables underpinning reactive strength in highly trained sprint athletes in comparison with a nonsprint–trained control group. Twelve highly trained sprint athletes and 12 nonsprint–trained participants performed drop jumps (DJs) from 0.25, 0.50, and 0.75 m onto a force plate. One familiarization session was followed by an experimental testing session within the same week. Reactive strength index (RSI), contact time, flight time, and leg stiffness were determined. Kinetic variables including force, power, and impulse were assessed within the braking and propulsive phases. Sprint-trained athletes demonstrated higher RSI vs. nonsprint–trained participants across all drop heights {3.02 vs. 2.02; ES (±90% confidence limit [CL]): 3.11 ± 0.86}. This difference was primarily attained by briefer contact times (0.16 vs. 0.22 seconds; effect size [ES]: −1.49 ± 0.53) with smaller differences observed for flight time (0.50 vs. 0.46 seconds; ES: 0.53 ± 0.58). Leg stiffness, braking and propulsive phase force, and power were higher in sprint-trained athletes. Very large differences were observed in mean braking force (51 vs. 38 N·kg −1 ; ES: 2.57 ± 0.73) which was closely associated with contact time ( r ±90% CL: −0.93 ± 0.05). Sprint-trained athletes exhibited superior reactive strength than nonsprint–trained participants. This was due to the ability to strike the ground with a stiffer leg spring, an enhanced expression of braking force, and possibly an increased utilization of elastic structures. The DJ kinetic analysis provides additional insight into the determinants of reactive strength which may inform subsequent testing and training.